2018
DOI: 10.1007/s12471-018-1117-1
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide on how to handle patients with bleeding events while on oral antithrombotic treatment

Abstract: Bleeding is a feared complication in patients who are treated with antithrombotic therapy (oral anticoagulation or antiplatelet therapy). Management of antithrombotic therapy after bleeding poses a dilemma where restarting the crucial medication could lead to recurrent bleeding, while interrupting or even discontinuing treatment could increase the thrombotic risk. In this review, we provide recommendations regarding the treatment of patients with a bleeding event while on oral antithrombotic therapy, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
0
21
0
1
Order By: Relevance
“…Enormous difficulties as to whether and when to restart medication are clearly evident in survivors [ 83 ]. In the large trials comparing new P2Y12 inhibitors to Clopidogrel, ICB was reported in only 0.3% of patients [ 8 , 9 ].…”
Section: Management Of Bleeding During Daptmentioning
confidence: 99%
See 1 more Smart Citation
“…Enormous difficulties as to whether and when to restart medication are clearly evident in survivors [ 83 ]. In the large trials comparing new P2Y12 inhibitors to Clopidogrel, ICB was reported in only 0.3% of patients [ 8 , 9 ].…”
Section: Management Of Bleeding During Daptmentioning
confidence: 99%
“…Due to the scarce number of ICB events in DAPT trials, we can only presume that DAPT might be reinitiated after approximately 4 weeks, with aspirin plus clopidogrel, and continued until the minimum advised duration [ 5 , 83 ]. Clearly, reassessment of clinical status, need for DAPT (time from ischemic event/revascularization), and team discussion with neurologist/radiologist/cardiologist should guide the decision making process.…”
Section: Management Of Bleeding During Daptmentioning
confidence: 99%
“…The specificity and sensitivity of the Technetium-99 RBC scan is 85% and 95% respectively in children and 60% and 9% respectively in adults. 18 These statistics elucidate the greater difficulty of establishing a diagnosis of MD in the adult population. The reduced sensitivity in adults is partly due to the reduced likelihood of an adult MD to express ectopic gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the case of emergency or urgent CABG, DAPT should be discontinued prematurely 11 . The discontinuation of DAPT might increase the risk of a thrombotic event 12 . However, delay in CABG had also been shown to associate with poor clinical outcome and increased risk of mortality 13 .…”
Section: Introductionmentioning
confidence: 99%